The Predictive Value of Phadiatop Paediatric in the Determination of Atopy in Allergic Diseases in Children - Ariyanto Harsono; Gunadi Santosa; Makmuri M. S. (Indonesian Pediatric Society Publishing House, 2019)
We obtained 28 patients with asthma bronchiole in this study. The presumptive diagnosis of allergy was made on the basis of history and physical examination. The positive result of the skin test to inhalant extracts and positive history of inhalant allergy add a confirmatory evidence in the diagnosis of inhalant allergy. The diagnosis of food allergy was judged by positive result in the provocation test. This study provided 15 patients with food allergy and 13 patients with food and inhalant allergy. House dust a1Jd mites were the most prevalent positive result in the skin test. While in the provocation test, egg ·and milk were found as the most prevalent food causing symptoms of allergy. The skin test predicted the atopy with an efficiency of 53.5%, While Phadiatop Paediatric predicted the atopy with an efficiency of 82.1 %. We concluded, as a screening procedure in allergy, the Phadiatop Paediatric is better than the skin test. Nevertheless the skin test has its superiority in the development of logical environmental controls and as a guide to immunotherapy in inhalant allergy.